Mastering embedded Linux programming : harness the power of Linux to create versatile and robust embedded solutions - Simmonds, Chris (Packt Publishing, 2015)
Annotation Harness the power of Linux to create versatile and robust embedded solutionsAbout This Book Create efficient and secure embedded devices using Linux Minimize project costs by using open source tools and programs Explore each component technology in depth, using sample implementations as a guideWho This Book Is ForThis book is ideal for Linux developers and system programmers who are already familiar with embedded systems and who want to know how to create best-in-class devices. A basic understanding of C programming and experience with systems programming is needed. What You Will Learn Understand the role of the Linux kernel and select an appropriate role for your application Use Buildroot and Yocto to create embedded Linux systems quickly and efficiently Create customized bootloaders using U-Boot Employ perf and ftrace to identify performance bottlenecks Understand device trees and make changes to accommodate new hardware on your device Write applications that interact with Linux device drivers Design and write multi-threaded applications using POSIX threads Measure real-time latencies and tune the Linux kernel to minimize themIn DetailMastering Embedded Linux Programming takes you through the product cycle and gives you an in-depth description of the components and options that are available at each stage. You will begin by learning about toolchains, bootloaders, the Linux kernel, and how to configure a root filesystem to create a basic working device. You will then learn how to use the two most commonly used build systems, Buildroot and Yocto, to speed up and simplify the development process. Building on this solid base, the next section considers how to make best use of raw NAND/NOR flash memory and managed flash eMMC chips, including mechanisms for increasing the lifetime of the devices and to perform reliable in-field updates. Next, you need to consider what techniques are best suited to writing applications for your device. We will then see how functions are split between processes and the usage of POSIX threads, which have a big impact on the responsiveness and performance of the final device The closing sections look at the techniques available to developers for profiling and tracing applications and kernel code using perf and ftrace. Style and approach This book is an easy-to-follow and pragmatic guide consisting of an in-depth analysis of the implementation of embedded devices. Each topic has a logical approach to it; this coupled with hints and best practices helps you understand embedded Linux better.
Includes index.
Keywords: Linux.; Linux; Computer programming.; elektronické knihy; electronic books